Lot-to-lot consistency, immunogenicity, and safety of the Ad26.ZEBOV, MVA-BN-Filo Ebola virus vaccine regimen: A phase 3, randomized, double-blind, placebo-controlled trial - Goldstein, Neil; McLean, Chelsea; Gaddah, Auguste; Doua, Joachim; Keshinro, Babajide; Bus-Jacobs, Linda; Hendriks, Jenny; Luhn, Kerstin; Robinson, Cynthia; Douoguih, Macaya (Human vaccines & immunotherapeutics, 2024)
This phase-3, double-blind, placebo-controlled study (NCT04228783) evaluated lot-to-lot consistency of the Ad26.ZEBOV, MVA-BN-Filo Ebola vaccine regimen. Participants were randomized (6:6:6:1) to receive the two-dose regimen from three consecutively manufactured lots of Ad26.ZEBOV on Day 1 paired with three consecutively manufactured lots of MVA-BN-Filo on Day 57 (Groups 1-3) or two doses of placebo (Group 4). An additional cohort also received an Ad26.ZEBOV booster or placebo 4 months post-dose 2. Equivalence of the immunogenicity at 21 days post-dose 2 between any two groups was demonstrated if the 95% confidence interval (CI) of the Ebola virus glycoprotein (EBOV GP)-binding antibody geometric mean concentration (GMC) ratio was entirely within the prespecified margin of 0.5-2.0. Lot-to-lot consistency (i.e., consecutive lots can be consistently manufactured) was accomplished if equivalence was shown for all three pairwise comparisons. Results showed that the primary objective in the per-protocol immunogenicity subset (n = 549) was established for each pairwise comparison (Group 1 vs 2: GMC ratio = 0.9 [95% CI: 0.8, 1.1], Group 1 vs 3: 0.9 [0.8, 1.1], Group 2 vs 3: 1.0 [0.9, 1.2]). Equivalence of the three groups for the Ad26.ZEBOV component only was also demonstrated at 56 days post-dose 1. EBOV GP-binding antibody responses (post-vaccination concentrations >2.5-fold from baseline) were observed in 419/421 (99.5%) vaccine recipients at 21 days post-dose 2 and 445/460 (96.7%) at 56 days post-dose 1. In the booster cohort (n = 39), GMCs increased 9.0- and 11.8-fold at 7 and 21 days post-booster, respectively, versus pre-booster. Ad26.ZEBOV, MVA-BN-Filo was well tolerated, and no safety issues were identified.